PENINGKATAN HASIL BELAJAR MATA PELAJARAN IPS MELALUI MODEL E-LEARNING DENGAN MEDIA VIDEO PADA SISWA KELAS VI-A MIN 1 BANDAR LAMPUNG - Aslaida, Aslaida (CV Sintesia, 2024)
This research aims to describe the increase in learning outcomes through the E-Learning Model with Video Media. This research was related to the research subjects to students of class VI-A in Madrasah Ibtidaiyah Negeri 1 Bandar Lampung Semester I of the 2020/2021 School Year as many as 30 students, consisting of 9 male students and 21 female students. The method used is Class Action Research (PTK) with research design using kemmis and Mc. Taggart models consisting of planning, implementation, observation, reflection. Data collection techniques using interviews, observations, field records and tests. From the results of research on the pre-cycle of student learning outcomes showed 43% completion. Then increases in cycles I through II that is, cycle I (67%) and cycle II (90%). The conclusion of this study is that through the use of E-Learning Model with Video Media can improve the learning outcomes of students of class VI-A Madrasah Ibtidaiyah Negeri 1 Bandar Lampung Semester I Year of Study 2020/2021.